Industry 4.0 technologies in a brazilian furniture industry - Schreiber, Dusan; Froehlich, Cristiane; Feil, Alexandre André; Becker, Vilson José (Revista de Administração da UFSM, 2024)
Purpose: The objective of this study is to analyze the technical feasibility of adopting I4.0 technologies in a large furniture industry located in the southern region of Brazil. Design/methodology/approach: Strategy research is a single case study, qualitative approach, collecting empirical data through in-depth interviews, participant observation, and a documental survey submitted to content analysis. Findings: Results evidenced that technologies I4.0 were considered technically viable for adoption in the company, and some of these technologies have already been adopted in some of its operations, such as IoT, big data, Cyber-physical Systems (CPS), Additive Manufacturing (AM)/3D printing, cloud computing, and vertical integration. On the other hand, RFID, collaborative robots, digital twins, augmented reality, and AI present technical feasibility but have not yet been adopted. Research limitations/implication: The limitation of the research stems from the strategy option for the case study, which restricts the possibility of generalizing the results obtained. Practical implications: The results of the study provide a review of the operational processes of the furniture industry, with the aim of identifying industry 4.0 technologies that can be adopted from the perspective of cost-benefit ratio. Originality/value: The increasing integration of the Internet of Things (IoT) in the industrial segment enables a new industrial era. However, furniture manufacturing is in the initial stages of adopting these technologies. The study addresses a topic that still represents a taboo in the corporate environment of the industrial sector in question and therefore offers elements for debate.